2018
DOI: 10.2147/ijn.s157805
|View full text |Cite|
|
Sign up to set email alerts
|

miR-221 suppression through nanoparticle-based miRNA delivery system for hepatocellular carcinoma therapy and its diagnosis as a potential biomarker

Abstract: BackgroundMicroRNA-221(miR-221) is frequently dysregulated in cancer. The purpose of this study was to explore whether miR-221 can be used as a potential diagnostic marker or therapeutic target for hepatocellular carcinoma (HCC).MethodsIn this study, we investigated whether miR-221 expression was associated with clini-copathological characteristics and prognosis in HCC patients, and we developed a nanoparticle-based miRNA delivery system and detected its therapeutic efficacy in vitro and in vivo.ResultsWe foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Given that miR-221/222 are increased in HCC the targeted inhibition of miR-221/222 by locked nucleic acid (LNA)-anti-miRNA paves the way to clinical applications [ 10 ]. Since RNA is a gene regulator that can be edited, it has the potential to be translated to the clinical practice.…”
mentioning
confidence: 99%
“…Given that miR-221/222 are increased in HCC the targeted inhibition of miR-221/222 by locked nucleic acid (LNA)-anti-miRNA paves the way to clinical applications [ 10 ]. Since RNA is a gene regulator that can be edited, it has the potential to be translated to the clinical practice.…”
mentioning
confidence: 99%
“…Overexpression of miR-221 in hepatocytes enhanced cell proliferation due to a rapid S-phase entry and supported liver regeneration [203]. High expression of miR-221 in HCC patients also correlates with a poor survival [197,204]. It has been shown that miR-221 can promote EMT [205] as well as HCC cell migration [206].…”
Section: Microrna-221mentioning
confidence: 99%
“…Hepatic stellate cells, in turn, can promote a pro-metastatic environment In HCC, miR-221 was also described in numerous studies to be a striking example of a highly potent oncogenic miRNA ( Figure 6). MiR-221 levels are enhanced in HCC tissues, HCC cell lines and in the serum of HCC patients [40,[197][198][199]. Therefore, likewise as in melanoma, miR-221 could also serve as a biomarker for the diagnosis of HCC [200].…”
Section: Microrna-221mentioning
confidence: 99%
“…Such a system was employed in a study by Li et al, who used nanoparticles with miR-221 mimic/inhibitor, both in vivo and in vitro, in order to track HCC development. Nanoparticle-based miR-221 inhibitors decrease cell proliferation, colony formation ability and tumor development, and result in lower serum levels of miR-221, thus representing a promising approach for HCC therapy [58]. Additionally, Cai et al demonstrated that a synergistic effect is achieved with the usage of a combination treatment regimen of nanoparticles containing anti-miR-221 and chemotherapeutic drugs, such as sorafenib [59].…”
Section: Mirna Spongesmentioning
confidence: 99%